HUBUNGAN STRES KERJA DENGAN BEBAN KERJA PADA TENAGA PENDIDIK DI INDONESIA - Khofa Hikmah Dilla Jannah; Susilawati (CV. ADIBA AISHA AMIRA, 2025)
Educators are energy professionals whose job is to plan and implement the learning process, assess learning outcomes, conduct mentoring and training, and conduct research and community service. With the large workload experienced by educators, it will be concluded that work stress. That way, the purpose of this study is to analyze how much influence the workload of educators has so that work stress occurs. The research method used is a literature review study method by reviewing and reviewing several relevant previous studies as study material accessed on the Google Scholar database. The results of this study found that there is a relationship between workload and work stress.